Case report: unusual cause of difficulty in intubation and ventilation with asthmatic-like presentation of Endobronchial Tuberculosis - Seevaunnamtum, S. Praveenaseeva; Mohd Ariff@Ghazali, Nazhan Afeef; Wan Hassan, Wan Mohd Nazaruddin; Muhd Besari, Alwi; Nik Hassan, Nik Fariza Husna; Che Omar, Sanihah; Ali, Saedah; Mohd Zain, Rhendra Hardy; Mat Hassan, Mohd Erham; Nik Mohamad, Nik Abdullah (Elsevier Ltd., 2017)
Endobronchial Tuberculosis is hazardous in causing circumferential narrowing of tracheobronchial tree despitethe eradication of tubercle bacilli in the initial insult from Pulmonary Tuberculosis. They may present astreatment resistant bronchial asthma and pose challenge to airway management in the acute setting. We presenta 25 year-old lady who was newly diagnosed bronchial asthma with a past history of Pulmonary Tuberculosisthat had completed treatment. She presented with sudden onset of difficulty breathing associated with noisybreathing for 3 days and hoarseness of voice for 6 months. Due to resistant bronchospasm, attempts were madeto secure the airway which led to unanticipated difficult intubation and ventilation. Subsequent investigationsconfirmed the diagnosis of Endobronchial Tuberculosis and patient was managed successfully with anti TBmedication, corticosteroids and multiple sessions of tracheal dilatation for tracheal stenosis. This case highlightsthe unusual cause of difficulty in intubation and ventilation due to Endobronchial Tuberculosis, which requiredmedical and surgical intervention to improve the condition.